Cytotoxic lactam and naphthoquinone alkaloids from roots of Goniothalamus lanceolatus Miq. - Rasol, Nurulfazlina Edayah; Ahmad, Fasihuddin Badruddin; Lim, Xiangyin; Chung, Felicia Fei Lei; Leong, Cheeonn; Mai, Chun Wai; Bihud, Nur Vicky; Zaki, Hamizah Mohd; Ismail, Nor Hadiani (Elsevier Ltd, 2018)
Two new alkaloids, (−)-goniolanceolactam (1) and 2-acetyl-3-amino-1,4-naphthoquinone (2), along with two known naphthoquinone alkaloids, 2-acetyl-3-amino-5-hydroxy-1,4-naphthoquinone (3) and cleistopholine (4) were isolated from the cytotoxic, dichloromethane root extract of Goniothalamus lanceolatus (Annonaceae). The structures were elucidated by spectroscopic techniques and the absolute configuration of 1 was established by single-crystal X-ray diffraction. Alkaloid 1 showed cytotoxic activity on human colon and lung cancer cell lines with IC50 values ranging from 5.32 to 9.91 μM. © 2018 Phytochemical Society of Europe